Transitioning from DSM‐IV to DSM‐5: A systematic review of eating disorder prevalence assessment. Issue 11 (16th August 2016) - Lindvall Dahlgren, Camilla; Wisting, Line
ABSTRACT: Objective: The objective of this study was to systematically review the literature on assessment of eating disorder prevalence during the DSM‐IV era (1994–2015). Method: A PubMed search was conducted targeting articles on prevalence, incidence and epidemiology of eating disorders. The review was performed in accordance with PRISMA guidelines, and was limited to DSM‐IV based eating disorder diagnoses published between 1994 and 2015. Results: A total of 74 studies fulfilled inclusion criteria and were included in the study. Results yielded evidence of over 40 different assessment instruments used to assess eating disorder prevalence, with the EAT‐40 being the most commonly used screening instrument, and the SCID being the most frequently used interview. The vast majority of studies employed two‐stage designs, closely followed by clinical interviews. Observations of higher prevalence rates were found in studies employing self‐reports compared to two‐stage designs and interviews. Discussion: Eating disorder prevalence rates have varied significantly during the DSM‐IV era, and are dependent on assessment methods used and samples investigated. Following the transition to the DSM‐5, eating disorder prevalence will change, warranting novel approaches to assessment and treatment planning. © 2016 Wiley Periodicals, Inc.